Komoditas Perdagangan di Pelabuhan Internasional Samudra Pasai pada Masa Dulu dan Masa Kini - Inagurasi, Libra Hari (Kapata Arkeologi, 2025)
Samudra Pasai, the first Islamic kingdom in Indonesia, was influenced by the discovery of maritime trade routes stretching from the Red Sea to India and through the Malacca Strait to China. Strategically located on the edge of the Malacca Strait, the kingdom developed into a maritime hub, serving as a harbor, commercial city, and a haven for traders from around the world. As a center of commerce, Samudra Pasai became known for its variety of trade commodities. This study aims to provide an overview of these commodities through cultural expressions, historical records, and their continuity in the present. Data were collected through field observations, interviews, and literature reviews, incorporating archaeological, historical, and ethnographic approaches. The research identifies three categories of commodities in the kingdom: foreign commodities, local commodities, and the continued export of local goods in the present day. Artifacts of foreign trade include ceramics and tombstones, while local commodities consist of pottery, salt, and pepper. Pottery from Samudra Pasai is believed to have been used as storage containers and measuring units for trade goods like salt and pepper, with pepper serving as a key export commodity. Today, the production of pottery, salt, and pepper cultivation around the Samudra Pasai site continues as an economic activity, suggesting a cultural and economic continuity from the kingdom’s historical period.